Reclaiming Slowness in Journalism: Critique, complexity and difference. (18th May 2016) - Craig, Geoffrey
Abstract : This article outlines an argument for the value of slowness in journalism. It makes an initial argument that our experiences of modernity are not singular experiences of speed and geographical dislocation but increasingly complex negotiations of different temporalities and spatial contexts and given this we also require different forms of fast and slow journalism. The article explores how journalism operates at particular speeds because of the comparative advantage of timeliness and also because there is a need for journalism to align itself with the temporalities of the institutional fields on which it reports. It discusses how various types of slow journalism act as interventions in the field of journalism, highlighting the political economy of fast journalism, and providing an alternative to dominant forms of contemporary journalistic practice. The article then focuses on the necessity and importance of slowness within contemporary journalism through a discussion of the concepts of critique, complexity and difference. It is argued that slowness is required for the journalistic task of critiquing power relations that are increasingly manifested in the mastery of the speed of public life. It is also argued that slowness in journalistic practice helps in offering effective scrutiny of public issues that are characterized by informational and conceptual complexity. Finally, it is argued that contemporary democracies involve growing levels of pluralism and proliferations of difference and that slowness is necessary in the representations and understandings of diverse identities, value systems and cultural practices.